Intratumoral CD103+ CD8+ T cells predict response to PD-L1 blockade. Issue 4 (7th April 2021) - Banchereau, Romain; Chitre, Avantika S.; Scherl, Alexis; Wu, Thomas D.; Patil, Namrata S.; de Almeida, Patricia; Kadel, III, Edward E.; Madireddi, Shravan; Au-Yeung, Amelia; Takahashi, Chikara; Chen, Ying-Jiun; Modrusan, Zora; et al.
Abstract : Background: CD8+ tissue-resident memory T (TRM ) cells, marked by CD103 ( ITGAE ) expression, are thought to actively suppress cancer progression, leading to the hypothesis that their presence in tumors may predict response to immunotherapy. Methods: Here, we test this by combining high-dimensional single-cell modalities with bulk tumor transcriptomics from 1868 patients enrolled in lung and bladder cancer clinical trials of atezolizumab (anti-programmed cell death ligand 1 (PD-L1)). Results: ITGAE was identified as the most significantly upregulated gene in inflamed tumors. Tumor CD103+ CD8+ TRM cells exhibited a complex phenotype defined by the expression of checkpoint regulators, cytotoxic proteins, and increased clonal expansion. Conclusions: Our analyses indeed demonstrate that the presence of CD103+ CD8+ TRM cells, quantified by tracking intratumoral CD103 expression, can predict treatment outcome, suggesting that patients who respond to PD-1/PD-L1 blockade are those who exhibit an ongoing antitumor T-cell response.